TEKNIK RELAKSASI NAFAS DALAM DAN TERAPI MUSIK SEBAGAI UPAYA PENURUNAN INTENSITAS NYERI HAID (DYSMENORRHEA) - Noor Azizah; Ana Zumrotun Nisak; Fania Nurul Khoirun Nisa (Universitas Muhammadiyah Semarang, 2015)
Background: Dismenorea or menstruation pain is the pain that is felt in the lower abdomen and thigh. This happens because an imbalance of the hormone progesterone in the blood causing pain arises.Almost the woman and young women must have felt at the time of menstrual disorders such as Dismenorea. The objective of the research is to determine the effect of deep breathing relaxation and music therapy to the intensity of menstrual pain (Dismenorea). The design of this study is quasi-experimental, pre-post test with control group.The sample of this study was all of girl students in MTs. Hidayatul Mustafidin who have ever got dismenorea. They are 56 students and divided into 28 students for experimental group and 28 students for control group. The result of this study is most of the respondents who are 14 years old, 62,5%. Moreover, the first menstruation (menarche) in 12 years old are 41,1%. The average pain scale before music therapy is 2,18 and after music therapy is 1.25. The average pain scale before deep breath relaxation is 2.21 and after deep breath relaxation is 1.25. The result of wilcozon test is p <0.05. Therefore, there is significance difference of the menstrual pain between before relaxation and after music therapy. The result of wilcozon test is p <0.05. Therefore, there is significance difference of the menstrual pain between before relaxation and after deep breath relaxation. It can be concluded that there a significance difference between deep breath relaxation and music therapy to decrease the menstrual pain scale. Suggested to the education field, to provide information that menstrual pain doesn’t interfere the learning activity.Keywords: breathing relaxation, music theraphy, dysmenorrheal